Bloom syndrome sans characteristic facial features in a mestizo patient- a diagnostic challenge - Chávez Álvarez, Sonia; Villarreal Martínez, Alejandra; Velasco Campo, Ma. del Roble; Moreno Vega, Isabel; Martínez de Villarreal, Laura Elia; Herz Ruelas, Maira Elizabeth; Ocampo Candiani, Jorge; Campos Acevedo, Luis Daniel (Indian Association of Dermatologists, Venereologists and Leprologists, 2019)
Bloom syndrome is a rare dermatosis, clinically diagnosed by characteristic cutaneous features, many of them affecting the face. The expected phenotype is a small for age patient with micrognatia, dolichocephaly, malar erythema, photosensitivity, multiple café‑au‑lait macules, and immunodeficiency. Here we present a 12‑year‑old Mestizo patient with clinical features of Bloom syndrome devoid of malar erythema and photosensitivity. This case illustrates that Bloom syndrome should be suspected even in the absence of hallmark facial erythema, especially in the Latin and Asian populations.